Tableting and dissolution characteristics of mixed fruit powder - Saifullah, M.; Yusof, Yus Aniza; Chin, Nyuk Ling; Aziz, M. G.; P. Mohammed, Mohd Afandi; Ab. Aziz, Norashikin (Elsevier, 2014)
In this study four types fruit powder were mixed together in a 1:1 ratio and tableting was carried out by direct compaction method. Two types tablet were produced, normal mix fruit powder tablet and fruit powder effervescent tablet. Compressibility of the powder mixtures were observed by using Kawakita and Lüdde equation. Normal fruit powder mixture was more compressible rather than fruit powder mixture with effervescent agent. Dissolution test was carried out in the dissolution medium of distilled water and simulated saliva fluid at room temperature and 37.5 °C temperature, respectively. Fruit powder effervescent tablet was dissolved faster in simulated saliva.